Perencanaan Program Kesiswaan Yang Berkelanjutan Dalam Menyongsong Tuntutan Era Digital - Yolanda, Dilla Desvi; Junaidi, Junaidi (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
This research identifies several important factors to consider in planning sustainable student programs in the digital age. These factors include the integration of technology in learning, the development of digital competencies for teachers and students, equitable accessibility of technology, protection of student data, the development of relevant curricula, collaboration with external parties, and the maintenance of a balance between technology use and healthy social interaction. Through a literature study approach, this study also identifies several recommendations for the development of sustainable student program planning in the digital era. The recommendations include training and developing digital competencies for teachers, increased access to technology for all students, protection of student data, integration of technology in the curriculum, collaboration between schools and external partners, and emphasis on fundamental educational values.